STUDI EKSPERIMEN ATAS KEKUATAN PENGHUBUNG GESER TIPE LEKATAN DARI TULANGAN BAJA LUNAK BERBENTUK SPIRAL - Sugupta, Dewa P.G.; Deskarta, Putu; Janitra Suardian, Adi (Jurnal Ilmiah Teknik Sipil, 2012)
This study was an experimental study on spiral-shaped bond shear connector that is used in steel-concrete composite beams. Spiral is made of mild steel reinforcement that has the same dimension between its diameter and its feet distance (single spiral). Specimens was designed according to Austaralian Standar AS 2327, Part 1, 1980 consisting of I shape steel profile and two concrete slabs attached to the flanges of the profile. Four types or groups of specimens were made with the same strength of concrete (27.65 MPa) and steel. Two spirals with diameter of 2 inch, 2.5 inch, 3 inch and 3.5 inch were applied in each specimen respectively and each group of specimen was consisted of three identical specimens. Then the specimens were tested by the pushout test method until failure. The results of experimental study shows that this type bond shear connector that was made of steel reinforcing bars had given strength to bear shear force. All specimens experienced failure purely due to the slip (bond failure) between the spiral and concrete. Moreover, in elastic conditions there was no real different behavior among the specimen groups. Differences in behavior occured at postelastic condition that was started from the compression force value of 120 kN (60 kN for each spiral). The value of the failure compressive force for specimen group I, II, III and IV were 160 kN, 170 kN, 175 kN and 180 kN, respectively revealing that there was consistency condition between the length of bond and the value of the failuer forces.
Keywords: Bond Shear Connector, Spiral Shape, Strength, Composite Structure